Improving the Antioxidant Properties of Calophyllum inophyllum Seed Oil from French Polynesia: Development and Biological Applications of Resinous Ethanol-Soluble Extracts - Mathieu Cassien; Anne Mercier; Sophie Thétiot-Laurent; Marcel Culcasi; Emilie Ricquebourg; Alice Asteian; Gaëtan Herbette; Jean-Pierre Bianchini; Phila Raharivelomanana; Sylvia Pietri (Antioxidants, 2021)
Tamanu oil from Calophyllum inophyllum L. has long been used in traditional medicine. Ethanol extraction was found the best strategy for recovering bioactive compounds from the resin part of Tamanu oil, yielding two neutral and acidic resins fractions with high phenolics, flavonoids and pyranocoumarins concentrations. A further cascade of LPLC/HPLC separations of neutral and acidic resin fractions allowed identifying fifteen metabolites, and among them, calanolide D and 12-oxocalanolide A (both in neutral fraction) were first identified from a natural source. All these extracts, subfractions and isolated metabolites demonstrated increased free radical scavenging, antioxidant, anti-inflammatory, antimicrobial and antimycobacterial activity compared to Tamanu oil and its de-resinated lipid phase. Overall, these results could promote resinous ethanol-soluble Tamanu oil extracts as a useful multifaceted and renewable medicinal resource.